SEISMIC SAFETY EVALUATION AND SVD BASED REMEDY RECOMMENDATION OF EXISTING R.C.C RESIDENTIAL BUILDINGS IN SOUTH INDIA (ASEAN Engineering Journal, 2025)
The project aims to enhance seismic safety in high-risk areas of Tamil Nadu, India, by conducting evaluations of 10 existing reinforced concrete buildings. The evaluation process starts with rapid visual screening, which is used to identify the buildings which require further evaluations. Buildings selected for further assessment are modelled in structural analysis software, ETABS to carry out seismic analysis using linear analysis methods such as equivalent static and response spectrum methods. The next step is to perform a non-linear time-history analysis to evaluate the behavior of buildings under low to moderate ground motions. Finally, deficiencies in the buildings are identified, and retrofitting techniques are suggested. A key innovation lies in the use of machine learning, specifically Singular Valued Decomposition (SVD) based Collaborative Filtering (CF) recommendation approach, to provide tailored retrofitting suggestions, enhancing the effectiveness of seismic safety interventions, which may include strengthening existing structural components, adding damping systems, or improving connections between different elements. The study results can guide similar buildings in the region, and retrofitting techniques can minimize property damage and save lives during future earthquakes. This project combines rapid visual screening, linear and non-linear analysis, machine learning and retrofitting suggestions to improve the seismic safety of buildings in high-risk areas in Tamil Nadu, India.